2010
DOI: 10.1002/anie.200905816
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Cross‐Coupling of Alkyl and Aryl Grignard Reagents with Alkynyl Halides

Abstract: 1 - ArticleGood old copper! A new general procedure to couple aliphatic and aromatic Grignard reagents with alkynyl halides under copper catalysis is described (see scheme; NMP=N-methylpyrrolidinone). The reaction is chemoselective and allows preparation of a vast array of simple and functionalized internal alkynes in high yields

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 111 publications
(40 citation statements)
references
References 29 publications
1
38
0
1
Order By: Relevance
“…[3] To solve this problem, several research groups have developed copper-catalyzed alkylation reactions of Grignard reagents. [3][4][5] It was found that these catalytic reactions are much easier to carry out and considerably less expensive. Additives, such as 1-methyl-2-pyrrolidinone and 1-phenylpropyne, were originally used to promote the alkylation reactions, [4] and the slow addition of the Grignard reagent was found to provide similar results in a recent study.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[3] To solve this problem, several research groups have developed copper-catalyzed alkylation reactions of Grignard reagents. [3][4][5] It was found that these catalytic reactions are much easier to carry out and considerably less expensive. Additives, such as 1-methyl-2-pyrrolidinone and 1-phenylpropyne, were originally used to promote the alkylation reactions, [4] and the slow addition of the Grignard reagent was found to provide similar results in a recent study.…”
mentioning
confidence: 99%
“…[3][4][5] It was found that these catalytic reactions are much easier to carry out and considerably less expensive. Additives, such as 1-methyl-2-pyrrolidinone and 1-phenylpropyne, were originally used to promote the alkylation reactions, [4] and the slow addition of the Grignard reagent was found to provide similar results in a recent study. [5] Although primary alkyl halides (as well as mesylates and tosylates) are mostly used in these catalytic alkylation reactions, some studies have indicated that secondary and even tertiary alkyl halides may also be possible coupling partners.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The spectroscopic data are in accordance with the published data. 20 General Procedure for the Preparation of Rhenacyclobutadiene Complexes. To a solution of Na[Re(CO) 5 ] (0.500 g, 1.43 mmol) in THF (20 mL) was slowly added one equivalent of methyl 3-(naphthalen-1-yl)propiolate (0.30 g, 1.43 mmol) in THF (20 mL) at RT.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…8 (s,OCH 3 ),124.0,126.6,126.8,127.5,127.6,127.7,129.9,130.1,135.0,148.2 (all s,C of Np), 156.9 (s, C(CO 2 Me)), 160.2 (s, CO 2 Me), 192.0 (s, trans-Re(CO)), 193.1 (s, Re(CO)), 194.8 (s, Re(CO)), 230.5 (s, ReC(Np)), 249.6 (s, ReC(OMe)). Elemental analysis (%) calcd for C 20 124.4, 126.6, 125.4, 125.5, 125.6, 127.7, 127.9, 132.8, 146.0 (all s, C of Np), 155.0 (s, C(CO 2 Me)), 158.1 (s, CO 2 Me), 190.0 (s, transRe(CO)), 190.9 (s, Re(CO)), 192.6 (s, Re(CO)), 227.5 (s, ReC(Np)), 244.8 (s, ReC(O n Pr)). Elemental analysis (%) calcd for C 22 General Procedure for the Reactions of Rhenacyclobutadiene Complexes with HCCOEt.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%